2001
DOI: 10.1089/105072501300042767
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor Expression in Cold and Hot Thyroid Nodules

Abstract: Hot thyroid nodules (HTNs) are predominantly caused by constitutively activating thyrotropin receptor (TSHR) mutations leading to an activation of the cyclic adenosine monophosphate (cAMP)-cascade that stimulates growth and function of thyroid epithelial cells and confers growth advantage. In contrast to HTNs, the molecular etiology of szintigraphically cold thyroid nodules (CTNs) is largely unknown. An increased prevalence of toxic multinodular goiters in iodine-deficient regions has been reported. Growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
4
7
0
1
Order By: Relevance
“…The values were similar regardless of whether the nodules were hot or cold (72). In other studies TGF-b1 was detected by immunohistochemistry and was found not only in thyrocytes but also in endothelial and connective tissue cells.…”
Section: Goiter and Benign Thyroid Tumorssupporting
confidence: 67%
“…The values were similar regardless of whether the nodules were hot or cold (72). In other studies TGF-b1 was detected by immunohistochemistry and was found not only in thyrocytes but also in endothelial and connective tissue cells.…”
Section: Goiter and Benign Thyroid Tumorssupporting
confidence: 67%
“…Eszlinger et al have found elevated IGF-1 levels in hot nodules, and suggested that this peptide may play a prominent role for selective growth advantages of hot or cold nodules (26). Our study has revealed no difference in the tissue levels of IGF-1 between hot and cold nodules.…”
Section: Discussionsupporting
confidence: 48%
“…Already in two former studies, we could identify differences in the expression of genes associated with the TGF-b signaling between AFTNs and their normal ST on protein-and mRNA-level. The investigation of TGF-b1 by ELISA revealed a significantly decreased TGF-b1 level in AFTNs in comparison to their STs (Eszlinger et al, 2001a) and a recent investigation of 588 genes by cDNA expression array showed a significantly decreased expression of the type III TGF-b receptor (betaglycan) in AFTNs (Eszlinger et al, 2001b). In addition, the differential expression of the type III TGF-b receptor was previously confirmed by real-time RT-PCR of 10 AFTNs and their ST (Eszlinger et al, 2001b).…”
Section: Genmapp Analysismentioning
confidence: 77%